2017
DOI: 10.37358/rc.17.2.5423
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Assessment of Mineralization Degree and Nutrient Content of Groundwater Bodies in Gorj County

Abstract: The research study performed aims to assess the degree of mineralization and nutrient contents of groundwater bodies in Gorj County in the period 2014-2015 based on the monitoring indicators such as: pH value, electrical conductivity, chlorides content, sulphates, nitrates, nitrites, phosphates, ammonium, sodium and potassium ions. Samples of waters were taken from eight wells located in depth groundwater bodies, code ROJi05 and ROJi08 in order to determine the mineral and nutrient contents. All the indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…From the treatment process perspective, the raw water quality is very important, depending on the pollution source, being simpler or more complicated [3][4][5]. Research conducted in Romania [6][7][8][9] showed that there are many cases of water sources in which the concentrations of inorganic nitrogen compounds (ammonium, nitrite, nitrate) exceed the imposed legislation values (0.5 mg/L, 50 mg/L, 0.1 mg/ L) in Europe and Romania [10], [11]. For medical or technological reasons, these compounds should be removed from the water until they reach maximum admissible limits.…”
mentioning
confidence: 99%
“…From the treatment process perspective, the raw water quality is very important, depending on the pollution source, being simpler or more complicated [3][4][5]. Research conducted in Romania [6][7][8][9] showed that there are many cases of water sources in which the concentrations of inorganic nitrogen compounds (ammonium, nitrite, nitrate) exceed the imposed legislation values (0.5 mg/L, 50 mg/L, 0.1 mg/ L) in Europe and Romania [10], [11]. For medical or technological reasons, these compounds should be removed from the water until they reach maximum admissible limits.…”
mentioning
confidence: 99%